The Impact of Stress and the Working Environment on Job Satisfaction and Decision Making among Women Entrepreneurs in Mexico - (:unkn) unknown (My University, 2013)
The world is changing and these changes have deeply affected the status of women as entrepreneurs; women’s working force is growing by the day along with their entrepreneurship, forcing women to find a balance between their jobs and their personal lives. This research analyses the degree of the impact of stress and the working environment on women entrepreneurs’ efficient decision-making and job satisfaction. An empirical investigation is carry out in four states in the Mexican Republic. It is using multiple regression analyses in SPSS. Results show that working environment impacts positively on women entrepreneurs’ efficient decision-making. This means that by having a good working environment, women entrepreneurs are able to have good relationships with workers in order to face decision.
Keywords: Women en Trepreneurs; Stress; Working Environment; Decision Making; Job Satisfaction; CIENCIAS SOCIALES [5]